2021
DOI: 10.1038/s41419-021-04301-7
|View full text |Cite
|
Sign up to set email alerts
|

p62/SQSTM1-induced caspase-8 aggresomes are essential for ionizing radiation-mediated apoptosis

Abstract: The autophagy–lysosome pathway and apoptosis constitute vital determinants of cell fate and engage in a complex interplay in both physiological and pathological conditions. Central to this interplay is the archetypal autophagic cargo adaptor p62/SQSTM1/Sequestosome-1 which mediates both cell survival and endoplasmic reticulum stress-induced apoptosis via aggregation of ubiquitinated caspase-8. Here, we investigated the role of p62-mediated apoptosis in head and neck squamous cell carcinoma (HNSCC), which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Lee et al ( 2021 ) and Cho et al ( 2021 ) were investigating the interplay between p62/SQSTM1 (Sequestosome 1) and HPV16 in HNSCC. Based on their experiments, Lee et al concluded that upon radiation treatments HPV16 + HNSCC cells fail to induce autophagic LC3 flux, as assessed by LC3B western blotting in cells that had been treated with Bafilomycin A1, and undergo apoptotic cell death (Lee et al 2021 ). Immunoblotting analyses showed no obvious difference in the expression level of p62 between HPV − and HPV16 + cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al ( 2021 ) and Cho et al ( 2021 ) were investigating the interplay between p62/SQSTM1 (Sequestosome 1) and HPV16 in HNSCC. Based on their experiments, Lee et al concluded that upon radiation treatments HPV16 + HNSCC cells fail to induce autophagic LC3 flux, as assessed by LC3B western blotting in cells that had been treated with Bafilomycin A1, and undergo apoptotic cell death (Lee et al 2021 ). Immunoblotting analyses showed no obvious difference in the expression level of p62 between HPV − and HPV16 + cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In head & neck squamous cell carcinoma cells, the autophagic cargo adapter p62/SQSTM1 is augmenting the activation and full processing of caspase 8 by capturing ubiquitinated caspase 8 into aggresome-like structures, necessary for subsequent apoptosis induction upon radiation treatment [ 22 ]. These findings raised the question if p62 is part of the apoptosis-inducing signaling pathway which is affected by A20 in TRAIL-resistant PDAC cells.…”
Section: Resultsmentioning
confidence: 99%
“…6D ). According to reports, the protein p62 was shown to activate caspase-8 [ 37 , 38 ]; and activated caspase-8 can cleave GSDMD to promote cell pyroptosis [ 39 , 40 ]. Thus, these results confirmed that DHEA exacerbates Nig-induced pyroptosis in LPS-primed macrophages via GPER activation, and the DHEA-caused pyroptosis may be related to p62-caspase-8-GSDMD pathway.…”
Section: Resultsmentioning
confidence: 99%